Impact of "high" implantation on functionality of self‐expandable bioprosthesis during the short‐ and long‐term outcome of patients who undergo transcatheter aortic valve implantation: Is high implantation beneficial?. Issue 3 (25th April 2018) - Vavuranakis, Manolis; Kariori, Maria; Scott, Lilly; Kalogeras, Konstantinos; Siasos, Gerasimos; Vrachatis, Dimitrios; Lavda, Maria; Kalantzis, Charalampos; Vavuranakis, Michael; Bei, Evangelia; Moldovan, Carmen‐Maria; Oikonomou, Evangelos; et al.
Summary: Aim: High position of the self‐expandable bioprosthesis CoreValve/Evolut R has been proved to affect immediate hemodynamics of the valve. Whether this may have any impact on long‐term procedural outcome has not been defined yet. The purpose of this study was to assess whether the final position of aortic bioprosthesis affects its long‐term functionality. Method: Consecutive patients (pts) who underwent successful TAVI procedure were evaluated and separated into 2 groups according to the implantation depth (ID): Group I: pts with 4 mm <ID ≤13 mm; Group II: pts with ID ≤4 mm. ID was measured utilizing the final aortography after device delivery and was defined as the distance both from the native non‐ and left coronary cusp to the deepest edge of the deployed bioprosthesis in the left ventricle. Clinical outcome and echocardiographic parameters were recorded before the procedure, at discharge, at 1‐month and 1‐year‐follow‐up. Results: One hundred and ninety‐eight pts (80 ± 5.5 years, 107 males [54%]) treated with the CoreValve/Evolut R bioprostheses were recorded. Group I appeared to have higher peak gradient (17 ± 6.5 vs 14 ± 5.5 mm Hg, P = .02) as well as V max (2 ± 0.4 vs 1.84 ± 0.38 m/s, P = .02) at follow‐up after 1 year when compared with Group II (ID <4 mm). Grouping for ID did not affect all‐cause 1‐year mortality. Paravalvular aortic regurgitation, as well as LVEF at discharge, proved to be independent predictors of all‐cause 1‐year mortality when adjusted for cofactors. Conclusion: Implantation depth under 4 mm seems to have a favorable effect on long‐term hemodynamic valve functionality.